Academic spoken English : a corpus-based guide to lectures, presentations, seminars and tutorials - Blanpain, Kristin, ....-; Laffut, An, ....- (Leuven : Acco, 2009)
In an internationalised academic environment, lecturers and researchers increasingly need to use English to give lectures and presentations, to participate in seminars and conferences and to coach international students. Academic Spoken English offers help in the following areas: - adapting a written text for a spoken register - expanding spoken academic vocabulary - using discourse markers, which structure the presentation for the audience - improving delivery (pace, clarity, interaction with the audience) - acquiring seminar skills (handling questions and comments) - improving grammatical and lexical accuracy - improving pronunciation (downloadable audio file) Examples and exercises are based on the MICASE Corpus and the John Swales Conference Corpus, extensive collections of transcripts of lectures and presentations, ensuring relevance and authenticity. The book can be used in the context of a presentation skills course or as a self-study resource.
Keywords: Engels -- Taalgebruik; Engelse taal -- Spreekvaardigheid -- Academisch niveau; Gesproken academisch Engels; Go international; International office; Mondelinge communicatie: Engels; Academic collection